Nasal Polyps: Integrating Homoeopathy and Surgical Approaches (Homoeopathy for All, 2026)
Nasal polyps are non-cancerous, inflammatory growths originating from the nasal mucosa, frequently causing symptoms such as nasal obstruction, anosmia (loss of smell), facial pain, and recurrent sinus infections. These benign lesions result from chronic inflammation of the nasal and sinus linings and often coexist with conditions like allergic rhinitis and asthma. Conventional treatment typically involves surgery, especially functional endoscopic sinus surgery (FESS), to physically remove large or persistent polyps. However, surgical intervention may not address underlying systemic causes, leading to frequent recurrence. This article explores nasal polyps from a homeopathic perspective, focusing on holistic, individualized treatment modalities that aim to correct systemic imbalances believed to contribute to polyp formation. Homeopathy offers remedies tailored to patients’ specific symptomatology and constitutional type, aiming to reduce inflammation, improve immune response, and alleviate the frequency and severity of symptoms. The integration of homeopathic treatment alongside surgery is discussed as a complementary approach to enhance patient outcomes. Homeopathic medicines may support symptom management, prevent or delay surgery, and promote faster post operative recovery by addressing both local and systemic factors. Recognizing the complementary roles of homeopathy and surgery can lead to more comprehensive management of nasal polyposis. This integrative approach potentially improves quality of life by reducing symptom burden, lowering recurrence rates, and supporting long-term respiratory health.
Keywords: Nasal polyps, Surgery, Nasal obstruction, Chronic inflam mation, Complementary therapy, Homoeopathic remedies